Delivery of Long Non-coding RNA NEAT1 by Peripheral Blood Monouclear Cells-Derived Exosomes Promotes the Occurrence of Rheumatoid Arthritis via the MicroRNA-23a/MDM2/SIRT6 Axis - Rao, Yujun; Fang, Yuxuan; Tan, Wei; Liu, Dan; Pang, Yubin; Wu, Xia; Zhang, Chunwang; Li, Guoqing (Frontiers in Cell and Developmental Biology, 2020)
Emerging evidence has pointed out the importance of long non-coding RNAs (lncRNAs) in multiple diseases, the knowledge of rheumatoid arthritis (RA)-associated lncRNAs remains limited. In this present study, we aimed to elucidate the mechanism of lncRNA nuclear paraspeckle assembly transcript 1 (NEAT1) from peripheral blood monouclear cell (PBMC)-derived exosomes (exos) on RA development by modulating the microRNA-23a (miR-23a)/murine double minute-2 (MDM2)/Sirtuin 6 (SIRT6) axis. RA was modeled in vivo by collagen induction in mice and in vitro by exposing fibroblast-like synoviocytes (FLSs) to lipopolysaccharide. Exos were isolated from human or mouse PBMCs, which were then were co-cultured with FLSs. Based on gain- and loss-of-function experiments, the cell proliferation and secretion of inflammatory factors were measured. LncRNA NEAT1 was found to be highly expressed in RA, and PBMCs-derived exos contributed to RA development by delivering lncRNA NEAT1. In lipopolysaccharide-induced FLSs, miR-23a inhibited the expression of MDM2, and overexpression of MDM2 partially rescued the inhibitory effect of miR-23a on FLS proliferation and inflammatory response. Mechanistically, MDM2 ubiquitination degraded SIRT6 in RA. LncRNA NEAT1 shuttled by PBMC-derived exos promoted FLS proliferation and inflammation through regulating the MDM2/SIRT6 axis. Furthermore, in vivo experiments suggested that downregulated lncRNA NEAT1 shuttled by PBMC-derived exos or upregulated miR-23a impeded RA deterioration in mice. This study highlights that lncRNA NEAT1 shuttled by PBMC-derived exos contributes to RA development with the involvement of the miR-23a/MDM2/SIRT6 axis.